2023
DOI: 10.3390/jcm12165368
|View full text |Cite
|
Sign up to set email alerts
|

Influences of Increasing Pedicle Screw Diameter on Widening Vertebral Pedicle Size during Surgery in Spinal Deformities in Children and Adolescents without Higher Risk of Pedicle and Vertebral Breaches

Pawel Grabala,
Ilkka J. Helenius,
Michal Grabala
et al.

Abstract: Background: A very common technique for treating spinal deformities in children and adolescents is the use of segmental screws. In order to obtain proper stability and the best possible correction, the screws must first be precisely inserted. Additional factors influencing the quality and success of the operation are the size and quality of the bone, the skills of the surgeon, and biomechanical factors, i.e., the width and length of the screws used during surgery. Our study was focused on evaluating the effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 48 publications
(87 reference statements)
1
10
0
Order By: Relevance
“…The available medical literature has often confirmed the greater stiffness of the structure, which was at least partially dependent on the diameter of the structure rod [58]. By using a thicker and stiffer rod, we are able to obtain greater corrective forces on the deformed spine, and in combination with larger sizes of pedicle screws and Ponte osteotomy of the posterior column of the spine, we will obtain the most desirable correction in three planes, as our study shows [22,23,30,57]. This trend persisted even after separating patients by curve flexibility.…”
Section: Discussionmentioning
confidence: 52%
See 4 more Smart Citations
“…The available medical literature has often confirmed the greater stiffness of the structure, which was at least partially dependent on the diameter of the structure rod [58]. By using a thicker and stiffer rod, we are able to obtain greater corrective forces on the deformed spine, and in combination with larger sizes of pedicle screws and Ponte osteotomy of the posterior column of the spine, we will obtain the most desirable correction in three planes, as our study shows [22,23,30,57]. This trend persisted even after separating patients by curve flexibility.…”
Section: Discussionmentioning
confidence: 52%
“…Segmental screw placement in the upper-and mid-thoracic spine is technically challenging, with high misplacement rates [51,59,60]. In particular, increased screw diameters are often avoided for pediatric thoracic vertebrae, given their smaller pediatric pedicle size [22,59,61]. In the study by Cho et al, the authors concluded that while large screw diameters (up to 9.5 mm) caused an increase in the pedicle circumference, there was no spinal canal compression [52].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations